Effects of Different Levels of Variability and Pressure Support Ventilation on Lung Function in Patients With Mild–Moderate Acute Respiratory Distress Syndrome - Ball, Lorenzo; Sutherasan, Yuda; Fiorito, Martina; Dall'Orto, Antonella; Maiello, Lorenzo; Vargas, Maria; Robba, Chiara; Brunetti, Iole; D'Antini, Davide; Raimondo, Pasquale; Huhle, Robert; Schultz, Marcus J.; et al. (Frontiers in Physiology, 2021)
Background: Variable pressure support ventilation (vPSV) is an assisted ventilation mode that varies the level of pressure support on a breath-by-breath basis to restore the physiological variability of breathing activity. We aimed to compare the effects of vPSV at different levels of variability and pressure support (ΔPS) in patients with acute respiratory distress syndrome (ARDS). Methods: This study was a crossover randomized clinical trial. We included patients with mild to moderate ARDS already ventilated in conventional pressure support ventilation (PSV). The study consisted of two blocks of interventions, and variability during vPSV was set as the coefficient of variation of the ΔPS level. In the first block, the effects of three levels of variability were tested at constant ΔPS: 0% (PSV0%, conventional PSV), 15% (vPSV15%), and 30% (vPSV30%). In the second block, two levels of variability (0% and variability set to achieve ±5 cmH2O variability) were tested at two ΔPS levels (baseline ΔPS and ΔPS reduced by 5 cmH2O from baseline). The following four ventilation strategies were tested in the second block: PSV with baseline ΔPS and 0% variability (PSVBL) or ±5 cmH2O variability (vPSVBL), PSV with ΔPS reduced by 5 cmH2O and 0% variability (PSV−5) or ±5 cmH2O variability (vPSV−5). Outcomes included gas exchange, respiratory mechanics, and patient-ventilator asynchronies. Results: The study enrolled 20 patients. In the first block of interventions, oxygenation and respiratory mechanics parameters did not differ between vPSV15% and vPSV30% compared with PSV0%. The variability of tidal volume (VT) was higher with vPSV15% and vPSV30% compared with PSV0%. The incidence of asynchronies and the variability of transpulmonary pressure (PL) were higher with vPSV30% compared with PSV0%. In the second block of interventions, different levels of pressure support with and without variability did not change oxygenation. The variability of VT and PL was higher with vPSV−5 compared with PSV−5, but not with vPSVBL compared with PSVBL. Conclusion: In patients with mild-moderate ARDS, the addition of variability did not improve oxygenation at different pressure support levels. Moreover, high variability levels were associated with worse patient-ventilator synchrony. Clinical Trial Registration:www.clinicaltrials.gov, identifier: NCT01683669.